Rehabilitative treatment of cleft lip and palate: experience of the Hospital for Rehabilitation of Craniofacial Anomalies - USP (HRAC-USP) - Part 2: Pediatric Dentistry and Orthodontics (Journal of Applied Oral Science, 2012)
The aim of this article is to present the pediatric dentistry and orthodontic treatment protocol of rehabilitation of cleft lip and palate patients performed at the Hospital for Rehabilitation of Craniofacial Anomalies - University of São Paulo (HRAC-USP). Pediatric dentistry provides oral health information and should be able to follow the child with cleft lip and palate since the first months of life until establishment of the mixed dentition, craniofacial growth and dentition development. Orthodontic intervention starts in the mixed dentition, at 8-9 years of age, for preparing the maxillary arch for secondary bone graft procedure (SBGP). At this stage, rapid maxillary expansion is performed and a fixed palatal retainer is delivered before SBGP. When the permanent dentition is completed, comprehensive orthodontic treatment is initiated aiming tooth alignment and space closure. Maxillary permanent canines are commonly moved mesially in order to substitute absent maxillary lateral incisors. Patients with complete cleft lip and palate and poor midface growth will require orthognatic surgery for reaching adequate anteroposterior interarch relationship and good facial esthetics.